2009
DOI: 10.1007/s00436-009-1462-5
|View full text |Cite
|
Sign up to set email alerts
|

One hundred years of research on the natural infection of freshwater snails by trematode larvae in Europe

Abstract: Research on the infection of snails by trematodes has been conducted in Europe for over a hundred years. The initial poor knowledge of the intra-molluscan stages of these parasites together with the difficulty of classifying them constituted a serious obstacle to the undertaking of integrated parasitological and malacological efforts to gain a better understanding of the phenomenon. The compilation of morphological and anatomical results of research on trematode larvae resulted in the publication of keys to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 75 publications
0
23
0
Order By: Relevance
“…Zdun 1959) and L. stagnalis (e.g. Bertman 1980;Żbikowska et al 2006;Żbikowska and Nowak 2009). A possible explanation might be that our samples were examined in May when snail mortality has already reduced the proportions of older cohorts in the snail populations and new cohorts have appeared.…”
Section: Small-scale Patterns Of Variationmentioning
confidence: 96%
See 2 more Smart Citations
“…Zdun 1959) and L. stagnalis (e.g. Bertman 1980;Żbikowska et al 2006;Żbikowska and Nowak 2009). A possible explanation might be that our samples were examined in May when snail mortality has already reduced the proportions of older cohorts in the snail populations and new cohorts have appeared.…”
Section: Small-scale Patterns Of Variationmentioning
confidence: 96%
“…Both species often co-occur in slow-moving or stagnant water bodies and both act as first intermediate hosts for a wide variety of larval trematodes. The morphology, life cycles and geographical distribution of these trematode larvae have been the subject of intense studies originating in Europe as early as the nineteenth century (reviewed in Faltýnková and Haas 2006;Faltýnková et al 2007Faltýnková et al , 2008aŻbikowska and Nowak 2009). A current cumulative estimate of the larval trematode richness based on extensive sampling in Central Europe (Faltýnková et al 2007(Faltýnková et al , 2008a and references therein) results in 37 species (23 in L. stagnalis and 15 in P. corneus) representing multiple evolutionarily independent lineages (13 families) (Table 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of parasite larvae infecting snails has revealed a huge diversity of helminths that can actually infect these hosts and enhanced the knowledge on diseases transmitted by molluscs (Żbikowska and Nowak 2009). The malacological surveillance of natural prevalences also gives insights into the higher and lower yearly infection levels and the identification of particular hosts for certain parasite species (Gürelli and Göçmen 2007;Mage et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…More intensive studies on the trematode infection of freshwater snails have been conducted in Europe since the beginning of the 20th century (¯BIKOWSKA & NOWAK 2009). However, many species revisions and introduction of new taxa caused serious difficulties when attempting to compare results of different authors.…”
Section: Introductionmentioning
confidence: 99%